2001
DOI: 10.1007/s004040000116
|View full text |Cite
|
Sign up to set email alerts
|

Sacrospinous ligament fixation for vaginal vault prolapse

Abstract: All 200 patients were analysed for intra- and postoperative complications. Urinary tract infection (n = 16, 8.0%), temporary irritation of the sciatic nerve (n = 15, 7.5%), temporary partial ureteral obstruction (n = 11, 5.5%) and blood loss less than 400 ml (n = 7, 3.5%), occurred in the postoperative phase. Long-term data (range from 6 months to 9 years, mean 4.8 years) exist for 123 patients. 119 were completely cured without any signs of urinary incontinence and prolapse. At follow-up 4 patients (3.25%) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 18 publications
1
35
1
10
Order By: Relevance
“…Other causes are congenital deficiency in the collagen vascular system, damage of pelvic floor during child birth process, or due to postmenopausal asthenia due to oestrogen deficiency. 8 Genital prolapse and vaginal vault prolapse following hysterectomy is one of the major concerns in perimenopausal and postmenopausal women and affect around 13% of women. This requires a simple, cost effective and safe operative procedure for prevention as well as for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes are congenital deficiency in the collagen vascular system, damage of pelvic floor during child birth process, or due to postmenopausal asthenia due to oestrogen deficiency. 8 Genital prolapse and vaginal vault prolapse following hysterectomy is one of the major concerns in perimenopausal and postmenopausal women and affect around 13% of women. This requires a simple, cost effective and safe operative procedure for prevention as well as for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several alternative operations for prolapse repair with uterine preservation, using either a vaginal or an abdominal approach, have been proposed (1,2,(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al reported a case series of seven women with no recurrence of prolapse at 9-17 months follow-up and also, Maher et al reported an objective success rate of 79% in 43 women after a mean follow-up of 12 months (1,16). Lantzsch et al described complications including massive haemorrhage, buttock pain and recurrent cystocele, and also Stepp and Paraiso described ureteral injury after uterosacral plication (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Esto corresponde a un 9% de recurrencia, lo que está dentro lo descrito en la literatura para esta técnica (2-19%) (11, [15][16][17][18]. Esta paciente presentaba los factores de riesgo más comunes para el prolapso genital: multiparidad, edad sobre 40 años y obesidad (19)(20).…”
Section: Preoperatoriosunclassified
“…Esto está por sobre la tasa de satisfacción de 76% descrita por Larson y cols (22). El aumento de la expectativa de vida conlleva un deterioro progresivo de la vida sexual de las pacientes, por lo que esta técnica quirúrgica es importante ya que conserva la capacidad de tener relaciones sexuales (17). Sin embargo, este ámbito no ha sido adecuadamente evaluado en la literatura y aunque esta técnica permita preservar la función sexual, el 73% de nuestras pacientes manifestaron no tener relaciones sexuales después de la cirugía (14).…”
Section: Preoperatoriosunclassified